2016
DOI: 10.1002/asia.201600423
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of Porphyrin–Paclitaxel Conjugates Into Nanomedicines: Enhanced Cytotoxicity due to Endosomal Escape

Abstract: Nanomedicines assembled directly from drug molecules possess several advantages, including precise molecular structure and high content of drugs. Herein, porphyrin-paclitaxel conjugates (Py-s-s-PTX) were synthesized by using a disulfide bond as a linker. The Py-s-s-PTX could self-assemble into nanoparticles (Py-s-s-PTX NPs) with a size of about 100 nm via disulfide-induced assembly. Py-s-s-PTX NPs are highly stable under biological conditions and could be destroyed in the presence of reducing agents as reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 47 publications
0
33
0
Order By: Relevance
“…The chemical conjugation of Taxol with porphyrin was conducted according to [17,29,43], as illustrated in Figure 4A. Briefly, tetracarboxyphenyl porphyrin (0.3 mM), N,N -dicyclohexylcarbodi imide (DCC) (0.25 mM), 4-dimethylaminopyridine (DMAP) (0.1 mM), and Taxol (0.2 mM) were dissolved in tetrahydrofuran (THF) (10 mL), and the mixture was then stirred in the dark at room temperature under nitrogen conditions for 72 h. The solution was filtered, and the filtrate was dried under the reduced pressure to remove the solvent.…”
Section: Conjugation Of Taxol With Porphyrinmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical conjugation of Taxol with porphyrin was conducted according to [17,29,43], as illustrated in Figure 4A. Briefly, tetracarboxyphenyl porphyrin (0.3 mM), N,N -dicyclohexylcarbodi imide (DCC) (0.25 mM), 4-dimethylaminopyridine (DMAP) (0.1 mM), and Taxol (0.2 mM) were dissolved in tetrahydrofuran (THF) (10 mL), and the mixture was then stirred in the dark at room temperature under nitrogen conditions for 72 h. The solution was filtered, and the filtrate was dried under the reduced pressure to remove the solvent.…”
Section: Conjugation Of Taxol With Porphyrinmentioning
confidence: 99%
“…With the global commercial and clinical values of Taxol, the side effect and required high doses are still the major challenges to this drug, especially in developing countries. Conjugation with various biocompatible polymers is a reliable approach to increase the efficiency of this drug and to reduce its side effects [17]. Porphyrin has been developed as a smart material for drug delivery, which can potentially decrease the side effects of the target drug, increasing its efficient activities.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the proton sponge effect, external stimuli, such as light, could also disrupt endosome to induce the enhanced cytotoxicity of anticancer drugs. For example, Xie et al 130 reported that small molecule nanodrugs self-assembled from porphyrin-paclitaxel conjugates could escape from endosome triggered by light irradiation. Under light irradiation, release of 1 O 2 damaged the endosome and then the released porphyrin-paclitaxel conjugates induced enhanced cancer therapy.…”
Section: Small Molecule Nanodrugs Overcoming Tumor Cell Barriermentioning
confidence: 99%
“…Haemolysis was determined from three independent experiments. The haemolytic ratio (HR) was calculated according to the following equation: Cellular uptake and distribution of Rg3 from the NPs were observed by CLSM (Leica, Germany) [32]. First, mPEG-Rg3-BSA NPs (180 μM) were labelled with FITC to investigate the uptake of NPs into L929 and HepG2 cells according to the method of Leamon and Low (1991).…”
Section: Haemolysis Assaymentioning
confidence: 99%